Development of Computer-Based Interactive Learning Media on Data Presentation Subject (Unnes Journal of Mathematics Education, 2022)
21st century learning students is required to be more active in learning than teachers, therefore this study aims to develop computer-based interactive learning media tutorials. This research used Research and Development (R & D) models and adapted from Borg and Gall. The learning media was validated by three validators using a validation sheet and obtained an average score is 3.55 (very valid) from the maximum scale of 4. Furthermore, revisions are made according to the suggestions and input of the validator. The revised learning media was tested with a questionnaire technique using a student response questionnaire sheet. The trial was carried out in two stages, namely product trials and usage trials. The first stage was product testing on six students and the percentage of practicality was 96.03%. The second stage was trial use on 28 students and the percentage was 97.62 (very practical). Then the product was revised according to the students' suggestions in the usage trial). Based on the analysis, it can be concluded that this computer-based mathematics learning media is valid and practical and can be used for students’ learning.